The Role of the Principal in Optimizing Teaching Factory Services in Vocational High Schools (SMK): A Study at SMK Negeri 3 Tondano - Rotty, Viktory N. J.; Ngadiorejo, Hartini; Sampouw, Nancy L.; Tengker, Irithca J.; Kalesaran, Renaldy J. (International Journal of Information Technology and Education, 2025)
The rapid development of industry and technology demands that vocational education adapt to produce graduates ready to compete in the job market. This study aims to analyze the role of the school principal in optimizing Teaching Factory (TeFa) services in Vocational High Schools (SMK), with a case study at SMK Negeri 3 Tondano. TeFa is a learning model based on real production activities that integrates education with the needs of the business and industrial sectors (DUDI). This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis involving several informants, including the principal, teachers, students, and industry partners. The findings show that the school principal has a strategic role in the planning, organizing, implementation, and evaluation of TeFa services. The principal exhibits visionary and transformational leadership that encourages innovation, collaboration with industry, and the strengthening of a productive work culture and entrepreneurial spirit within the school environment. Adapting the TeFa implementation based on the characteristics of each department is also a key strategy to enhance the relevance and effectiveness of learning. The principal also succeeded in overcoming challenges such as limited facilities, rigid regulations, and a lack of industry-experienced teachers through collaborative approaches and policy advocacy. Various innovative initiatives, such as digital management systems, the implementation of a multi-stakeholder engagement model, and the integration of curriculum with real project-based learning, demonstrate that school leadership is a determining factor in the successful implementation of TeFa. These findings highlight the essential role of school principals as change agents in creating adaptive, excellent, and competitive vocational education.